2020
DOI: 10.1093/ofid/ofaa427
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gram-Negative Bloodstream Infections in the Era of Rapid Diagnostic Testing: Impact With and Without Antibiotic Stewardship

Abstract: Background Verigene Blood-Culture Gram-Negative is a rapid diagnostic test (RDT) that detects GNs and resistance within hours from Gram-stain. The majority of data supports the use of RDTs with antimicrobial stewardship (AMS) intervention in gram-positive BSI; Less is known on for GN BSI. Methods Retrospective quasi-experimental (non-randomized) study of adult patients with RDT-target GN BSI comparing patients pre-RDT/AMS ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…The high efficiency and rate of performing microbiological research using an automatic analyzer for hemoculture in comparison with the traditional manual method has been shown. паратов, преобладанием среди пациентов людей пожилого возраста, а также появлением множественной устойчивости микроорганизмов к антибактериальным препаратам [2][3][4].…”
Section: Discussionunclassified
“…The high efficiency and rate of performing microbiological research using an automatic analyzer for hemoculture in comparison with the traditional manual method has been shown. паратов, преобладанием среди пациентов людей пожилого возраста, а также появлением множественной устойчивости микроорганизмов к антибактериальным препаратам [2][3][4].…”
Section: Discussionunclassified
“…The Verigene system (Luminex) uses multiplex PCRs and subsequent microarray hybridisation for detection of 22 bacteria and their resistance determinants from positive BC [ 57 , 58 ], and comprises two different panels, for Gram positives and Gram negatives, whose choice can be driven by the Gram stain results. Verigene has proved able to identify susceptibility to new β-lactam/β-lactamase inhibitors [ 59 ], and when implemented within an AMS program, reduced the time to optimal therapy in bacteraemic patients [ 60 , 61 ].…”
Section: New and Emerging Methodsmentioning
confidence: 99%
“…These studies have been previously summarized elsewhere and have been incorporated in meta-analyses (67)(68)(69). Limitations of these studies include their varying quality; small sample sizes; single-center, retrospective, and observational designs; and historical or absent control groups (70)(71)(72)(73). A few studies have used the more rigorous study design of a prospective randomized controlled trial (RCT) to evaluate outcomes of rapid blood culture AST methods and are summarized in Table 3.…”
Section: Clinical Impact Of Rapid Antimicrobial Susceptibility Testinmentioning
confidence: 99%
“…It is also notable that with the exception of the study by Kim et al, most of these trials were conducted in areas with low rates of antimicrobial-resistant bacteria, and it is possible that more clinical benefit would be observed in areas with higher rates of resistant infections (19,20). Additionally, most of the studies demonstrate the importance of pairing rapid blood culture diagnostics with antibiotic stewardship team review, as has been emphasized by many others (20,68,69,73,(77)(78)(79)(80). A meta-analysis of primarily observational studies demonstrated mortality benefit when blood culture diagnostics were used with stewardship programs but not without stewardship programs (69).…”
Section: Clinical Impact Of Rapid Antimicrobial Susceptibility Testinmentioning
confidence: 99%
See 1 more Smart Citation